5x-11=6x-11

Simple and best practice solution for 5x-11=6x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-11=6x-11 equation:


Simplifying
5x + -11 = 6x + -11

Reorder the terms:
-11 + 5x = 6x + -11

Reorder the terms:
-11 + 5x = -11 + 6x

Add '11' to each side of the equation.
-11 + 11 + 5x = -11 + 11 + 6x

Combine like terms: -11 + 11 = 0
0 + 5x = -11 + 11 + 6x
5x = -11 + 11 + 6x

Combine like terms: -11 + 11 = 0
5x = 0 + 6x
5x = 6x

Solving
5x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5x + -6x = 6x + -6x

Combine like terms: 5x + -6x = -1x
-1x = 6x + -6x

Combine like terms: 6x + -6x = 0
-1x = 0

Divide each side by '-1'.
x = 0

Simplifying
x = 0

See similar equations:

| 3x+12=16x-14 | | x-[-12]=-7 | | -7y+7=-4y-8 | | 49x^2-98x+33=0 | | 5/9d-9/10 | | h-[-8]=3 | | 64x^3-16x^2+12x=0 | | (1+n)+(5-4n)= | | 0=-16x^2+1600x-38400 | | 14=x+14 | | 4x*x-4x+1=3x+2 | | 0=-16t^2+1600x-38400 | | 9x=11x+30 | | (10z+4)-(9z+7)=-6 | | -18+34=-4(x+9) | | 5m^2-2m-1=0 | | -y+2x+4=0 | | 8=5x^2-3x | | |s+4|=3 | | 5x-8=13x+4 | | 25x^3+20x^2+x=-3x | | 8x+7-11x+10=10x-13x+11 | | -5/13x=-2 | | 4.3v+6=2.3v-2 | | 2(-3)+2y=20 | | -2(4x+3)-8=6+2x | | 36=18-8t | | (10x+4)-(9x+7)=-6 | | 2*x=1.5*13.3 | | 3(n+4)=-3(4+n) | | 5[7-5(6-q)]-7=7[(7q-6)+4]-50 | | (x^4-2.3x^3+6)(x^4-2.3x^3+6)=0 |

Equations solver categories